A century of suicide: Insights from long-term data in the United States - Nina de Lacy; Wai-yin Lam; Timothy Collins; David Danks; Fernando A. Wilson; Ken R. Smith; Bernice A. Pescosolido (Proceedings of the National Academy of Sciences, 2026)
The 2024 National Strategy for Suicide Prevention identifies suicide as “an urgent and growing public health crisis” driven partly by mental health and overdose rates, the COVID-19 pandemic, and declining social connectedness. Yet, data constraints have limited long-term investigations of suicide trends. Acknowledging limits in data sequence continuity, we constructed the Suicide Trends and Archival Comparative Knowledgebase (STACK), harmonizing data from 1900–2021. Coupling visualizations with Joinpoint regressions, we examine the contemporary suicide crisis in historical perspective. Data reveal patterns that both support and challenge prevailing understandings of suicide risk, trends, and drivers. Overall, we document a cyclical, dampening, and downward-trending pattern of suicide over 120 y, contrasting sharply with trends in other causes of death. However, this trend is offset by a sharp rise and unique patterning for persons under 35, beginning in the mid-to-late 1950s. The contemporary “youth crisis” spans a broader age range and begins much earlier than typically acknowledged. Each successive generation faces risk at younger ages, accompanied by a startling rise in suicide by hanging since the 1980s among both males and females. Despite ongoing concerns about rural populations and the elderly, living in large metropolitan areas (versus suburban and rural areas) and being older have recently emerged as protective factors. While analyses by race or rurality remain limited to the last half century because of data availability, the long-term temporal, geographic, and sociodemographic complexity of suicide mortality trends offers critical insights and intriguing avenues for next-generation research, treatment, and prevention efforts.